Pediatric Ovarian Growing Teratoma Syndrome. (1st June 2017) - Rentea, Rebecca M.; Varghese, Aaron; Ahmed, Atif; Kats, Alexander; Manalang, Michelle; Dowlut-McElroy, Tazim; Hendrickson, Richard J.
Abstract : Ovarian immature teratoma is a germ cell tumor that comprises less than 1% of ovarian cancers and is treated with surgical debulking and chemotherapy depending on stage. Growing teratoma syndrome (GTS) is the phenomenon of the growth of mature teratoma elements with normal tumor markers during or following chemotherapy for treatment of a malignant germ cell tumor. These tumors are associated with significant morbidity and mortality due to invasive and compressive growth as well as potential for malignant transformation. Current treatment modality is surgical resection. We discuss a 12-year-old female who presented following resection of a pure ovarian immature teratoma (grade 3, FIGO stage IIIC). Following chemotherapy and resection of a pelvic/liver recurrence demonstrating mature teratoma, she underwent molecular genetics based chemotherapeutic treatment. No standardized management protocol has been established for the treatment of GTS. The effect of chemotherapeutic agents for decreasing the volume of and prevention of expansion is unknown. We review in detail the history, diagnostic algorithm, and previous reported pediatric cases as well as treatment options for pediatric patients with GTS.